Addressing the Person of the Therapist in Supervision: The Therapist's Inner Conversation Method. Issue 2 (9th May 2016) - Rober, Peter
Abstract : In this study a method of retrospective case supervision is presented aimed at helping the supervisee to become a better self‐supervisor. The method pays special attention to the therapist's self‐reflection and has the therapist's inner conversation as a central concept. The starting point of the method is an assignment in which the supervisee reflects on a case using a tape‐assisted recall procedure. The method helps trainees to develop experiential expertise to become more flexible and effective therapists. A case example of one training group of novice family therapists illustrates the use of the method. Abstract : Translation into Spanish Video Abstract